Thrombin binding to GPIbα induces integrin αIIbβ3 dependent platelet adhesion to fibrin in ex vivo flowing whole blood - Dubois, Christophe; Reigner, Sylvie C. Meyer; Steiner, Beat; Riederer, Markus A. (Thrombosis and Haemostasis, 2004)
We have investigated the role of the thrombin/GPIbα interaction in the adhesion of platelets to fibrin in a whole blood ex vivo perfusion model at a shear rate of 280 s-1. Blood was perfused through parallel-plate chambers containing coverslips coated with cells expressing tissue factor, leading to the generation of thrombin and thus, deposition of fibrin onto the exposed cells. Adhesion of platelets to fibrin and thrombus growth were analyzed. Interestingly, when GPIbα was removed from the platelet surface by action of mocarhagin, platelet adhesion on fibrin was inhibited. Furthermore, a monoclonal antibody, VM16d, directed against the thrombin binding site on GPIbα also inhibited platelet adhesion on fibrin, showing the importance of the thrombin/GPIbα interaction. We then looked at the involvement of αIIbβ3 and showed that platelet adhesion and thrombus growth on fibrin were inhibited by the dodecapeptide, whereas lamifiban only inhibited the growth of the platelet thrombus. These results indicated that binding of thrombin to GPIbα induced an intracellular signaling leading to the interaction of the platelet integrin αIIbβ3 with the fibrindodecapeptide sequence.
Keywords: Platelet adhesion; GPIb-IX-V; thrombin; αIIbβ3; fibrin